Athermal influence of pulsed electric current on the twinning behavior of Mg–3Al–1Zn alloy during rolling. (15th March 2016) - Kuang, Jie; Du, Xinpeng; Li, Xiaohui; Yang, Yanyang; Luo, Alan A.; Tang, Guoyi
Abstract: Electroplastic rolling (ER) and conventional warm rolling (WR) were conducted on Mg–3Al–1Zn (AZ31) sheet to study, for the first time, the influence of pulsed electric current on the twinning behavior of magnesium alloy. The 10 1 ̅ 2 extension twins were found insensitive to the current. The primary 10 1 ̅ 1 contraction twins, in contrast, display higher number fraction of twinned grains and better Schmid behavior in ER than in WR. This difference indicates a special 'athermal' influence of the current, which probably originates from the improved strain accommodation due to enhanced prismatic < a > activity. The distinctive twinning behavior is related to the improved rollability. Graphical abstract: